2018
DOI: 10.1371/journal.ppat.1006996
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the molecular determinants of cholinergic anthelmintic sensitivity in nematodes: When novel functional validation approaches highlight major differences between the model Caenorhabditis elegans and parasitic species

Abstract: Cholinergic agonists such as levamisole and pyrantel are widely used as anthelmintics to treat parasitic nematode infestations. These drugs elicit spastic paralysis by activating acetylcholine receptors (AChRs) expressed in nematode body wall muscles. In the model nematode Caenorhabditis elegans, genetic screens led to the identification of five genes encoding levamisole-sensitive-AChR (L-AChR) subunits: unc-38, unc-63, unc-29, lev-1 and lev-8. These subunits form a functional L-AChR when heterologously expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 68 publications
4
68
0
Order By: Relevance
“…The L2 larvae obtained from in vitro culture of eggs were subjected to gene silencing assays. The RNAi experiments were performed on 3000-4000 L2 larvae in a final volume of 500 µL in 2 mL tubes as described previously [1,56]. First, to investigate the potential ingestion of siRNA constructs for gene silencing experiments, H. contortus L2 larvae were incubated (for 2 h at 20 • C under gentle agitation) in a culture medium containing 1 µM of a nonspecific siRNA targeting gfp (nonspecific).…”
Section: Rnai-based Silencing Of Candidate Genesmentioning
confidence: 99%
“…The L2 larvae obtained from in vitro culture of eggs were subjected to gene silencing assays. The RNAi experiments were performed on 3000-4000 L2 larvae in a final volume of 500 µL in 2 mL tubes as described previously [1,56]. First, to investigate the potential ingestion of siRNA constructs for gene silencing experiments, H. contortus L2 larvae were incubated (for 2 h at 20 • C under gentle agitation) in a culture medium containing 1 µM of a nonspecific siRNA targeting gfp (nonspecific).…”
Section: Rnai-based Silencing Of Candidate Genesmentioning
confidence: 99%
“…The roles of the various components of lipophilic molecule transport systems (passive diffusion, active influx, and active efflux) need to be investigated further, as well as the role and production of lipids in nematodes. This knowledge may therefore make it possible to identify new targets for anthelmintics, like other targets described in recent research in order to counter multiple resistance [8,14,46,53,57,79].…”
Section: Discussionmentioning
confidence: 96%
“…Resolving the contribution of AChRs antagonism to the observed anthelmintic effects would require additional experiments that are beyond the scope of this study. For such experiment, the knock-down of acetylcholine receptor expression by RNA interference 39 in parasitic larvae before further exposure to lupin alkaloids could be a method of choice. However, our results indicated that the E063 enriched alkaloidic fraction was not necessarily exerting as much inhibition as the total seed extract and that significant larval migration inhibition was associated with the non-alkaloid seed extract in that case.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the scarcity of fractionated alkaloidic compounds (2.7 to 12.8 mg), their anthelmintic effect on infective H. contortus larvae was measured using ALMA. This technic relies on larval auto-fluorescence generated through ultraviolet excitation 38,39 . Every alkaloidic compound was incubated for 4 hours at 20°C with 7,500 H. contortus infective larvae each.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation